2019
DOI: 10.1039/c9ta03601f
|View full text |Cite
|
Sign up to set email alerts
|

High energy density and high efficiency all-organic polymers with enhanced dipolar polarization

Abstract: The dielectric constant of polymers was increased by combining flexible segments and rigid polar segments in the polymer backbone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 27 publications
0
44
0
1
Order By: Relevance
“…The strategy for the design of a polymer having a stable dielectric constant and low polarization loss over a broad temperature range would require that all rigid segments having restricted rotation remain restricted while all freely rotatable single bonds continue to freely rotate across the entire temperature range for operation. [ 28,29 ] As such, close attention needs to be paid to elements that can be involved in conjugation. For example, an element that could result in partial double bond in conjugation with a sp 2 hybridized carbon could become freely rotating at a higher temperature, contributing to a temperature dependent polarization.…”
Section: Figurementioning
confidence: 99%
“…The strategy for the design of a polymer having a stable dielectric constant and low polarization loss over a broad temperature range would require that all rigid segments having restricted rotation remain restricted while all freely rotatable single bonds continue to freely rotate across the entire temperature range for operation. [ 28,29 ] As such, close attention needs to be paid to elements that can be involved in conjugation. For example, an element that could result in partial double bond in conjugation with a sp 2 hybridized carbon could become freely rotating at a higher temperature, contributing to a temperature dependent polarization.…”
Section: Figurementioning
confidence: 99%
“…Li et al. [ 103 ] further indicated that the dipolar polarization could be increased via incorporating flexible ether bonds into the main chain of PTUA, so that the ε r can reach 6.6. Feng et al.…”
Section: Dielectric Polymers For Film Capacitorsmentioning
confidence: 99%
“…However, their energy storage density is much lower than those of other energy storage devices, limiting further application. For example, as a representative commercial capacitor, the low dielectric constant (2.2) of biaxially oriented polypropylene (BOPP) restricts energy density to less than 4 J cm –3 . It is urgent to seek an effective way to develop dielectric materials with well breakdown characteristics and excellent energy storage characteristics and to meet the miniaturization, lightweight, and reliability requirements for future power electronic devices.…”
Section: Introductionmentioning
confidence: 99%